2001
DOI: 10.1006/mthe.2001.0287
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correction of Fanconi Anemia Group C Hematopoietic Cells by the Use of a Novel Lentiviral Vector

Abstract: Lentiviral vectors transduce nondividing hematopoietic cells more efficiently than other currently available vector systems. Here we report the results of human hematopoietic cell gene transfer using lentiviral vectors based upon human immunodeficiency virus (HIV-1) and equine infectious anemia virus (EIAV). EIAV is a nonprimate lentivirus and is severely restricted in its host range to horses and closely related equines. We employed the EIAV vector system to test for gene transfer to human Fanconi anemia (FA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…However, data from numerous laboratories have demonstrated that Fancc Ϫ/Ϫ mice require some myelopreparation in order to consistently engraft exogenous cells. 36,37 Further, in a phase 1 clinical trial, FANCC patients who received a transplant in the absence of any myelopreparation failed to have significant long-term proliferation of transduced cells. 9 The failure to engraft genetically corrected cells may in part be related to observations that in vitro-cultured cells frequently do not engraft as well as freshly isolated cells 38,39 or alternatively because of the relatively low number of stem cells that are transduced and transplanted compared with endogenous stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from numerous laboratories have demonstrated that Fancc Ϫ/Ϫ mice require some myelopreparation in order to consistently engraft exogenous cells. 36,37 Further, in a phase 1 clinical trial, FANCC patients who received a transplant in the absence of any myelopreparation failed to have significant long-term proliferation of transduced cells. 9 The failure to engraft genetically corrected cells may in part be related to observations that in vitro-cultured cells frequently do not engraft as well as freshly isolated cells 38,39 or alternatively because of the relatively low number of stem cells that are transduced and transplanted compared with endogenous stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Current options for titering lentiviral vectors include assessment of vector RNA in supernatant (RNA titer), 14 assessment of vector DNA in transduced cells (DNA titer), and expression of a transgene following transduction. 12,15,16 Assessing titer in vector supernatants is technically the easiest and provides the most rapid turnaround.…”
Section: -Fold) and Gfp Titers (~10 4 -Fold) To Show That The Lentivmentioning
confidence: 99%
“…In contrast to the similarities in the levels of gene transfer obtained with EIAV-and HIV-based vectors, gene expression from EIAVbased vectors was significantly less than that from HIV-based vectors, due to the relative instability of EIAV-derived mRNA transcripts. It is important to note that during the preparation of this paper, Yamada et al reported lower levels of EIAVderived mRNA than those derived from HIV vectors in a transduced human B-cell line (16). However, the mechanism for this difference in mRNA levels was not investigated.…”
mentioning
confidence: 92%